Prevalence of yeast species in the oral cavity and its relationship to dental caries - doi: 10.4025/actascihealthsci.v33i1.7712 - Adriane Castro Martinez Martins; Márcia Luzia Ferrarezi Maluf; Terezinha Inez Estivalet Svidzinski (Acta Scientiarum. Health Sciences, 2011)
The purpose of this study was to evaluate the frequency of yeasts in the oral cavity, and to determine the main yeast species present and whether there is a correlation between the presence of yeasts in the mouth and caries or dental plaque. Ninety-five healthy children and adolescents who were residents of rural villages participated in the study. They were submitted to an odontological examination for the identification of dental caries and dental plaque, as well as for yeast culture and identification. The frequency of yeasts was 33.7%, with no difference between females and males. Yeasts predominated in children (37.7%) more than in adolescents (26.5%). Caries and dental plaque were present in 70.3 and 96.8% of the sample, respectively, and Candida albicans was the most prevalent species (75%). The findings indicated a correlation between the presence of caries and yeasts in the mouth (p = 0.0087) and between yeasts and the number of carious teeth (p < 0.05). However, there was no correlation between yeasts and the dental plaque index (p = 0.49).